The effect of pouring time on the dimensional stability of casts made from conventional and extended-pour irreversible hydrocolloids by 3D modelling - Hasan Ö. Gümüş; Mehmet Dinçel; Süleyman K. Büyük; Halil İ. Kılınç; Mehmet S. Bilgin; M. Zortuk (Elsevier, 2015)
Background/purpose: The aim of this study was to determine the accuracy of casts made from irreversible hydrocolloid impressions with immediate and delayed pouring. Materials and methods: A master model was mounted on a modified articulator designed to standardize impression procedures. A total of 250 impressions were taken and grouped into 25 groups (n = 10) according to irreversible hydrocolloid material (CA37, Tropicalgin, ColorChange, Hydrogum 5, and Hydrocolor 5) and storage time (0 hours, 1 hour, 24 hours, 72 hours, and 120 hours). Impressions were stored at 23 ± 1°C and 100% relative humidity and poured with gypsum at the predetermined storage time. Casts were scanned with a three-dimensional (3D) model scanner. The digital models were measured and subtracted from the measurements obtained from the master model. The absolute values of dimensional differences were statistically analyzed using two-way analysis of variance (ANOVA) and post hoc Fisher LSD test (P < 0.05). Results: Different irreversible hydrocolloids and pouring times showed significant differences (P < 0.001). In all irreversible hydrocolloids, no statistically significant differences were found with impressions poured after 0 hours, 1 hour, and 24 hours of storage (P > 0.05). However, after 72 hours and 120 hours of storage, Tropicalgin and CA37 irreversible hydrocolloid impressions were found to be significantly different (P < 0.05). Moreover, ColorChange, Hydrogum 5, and Hydrocolor 5 irreversible hydrocolloid impressions were not statistically different up to 120 hours (P > 0.05). Conclusion: All of the conventional and extended-pour impression materials tested in this study can be poured up to 24 hours with accuracy, if impressions are correctly stored. Extended-pour impression materials (ColorChange, Hydrogum 5, and Hydrocolor 5) can be poured up to 120 hours, if stored correctly.